PENGARUH JUMLAH KREDIT, TABUNGAN, DEPOSITO, DAN PENGALAMAN BADAN PENGAWAS PADA PROFITABILITAS - Firna Erawati, Ida Ayu Komang; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2015)
Institute Pekreditan Village (LPD) in the economy of much help both economically and socially. LPD raising funds from the community in the form of savings and deposits. Savings and deposits is an important thing for LPD to be able to channel the funds back into the community in the form of credit. Research sites in Bangli district on the LPD. Data collection methods used h with non-behavioral observation method. The data analysiss technniqued useing a multiple linear analysiss. Based on the research results, it can be concluded simultaneously variable amount of credit, savings, deposits and regulatory bodies experience a significant effect on the profitability of the LPD in Bangli Regency and partial variable amount of credit, savings and regulatory bodies experience a significant effect on the profitability of the LPD, while deposits have no effect LPD on profitability in Bangli regency.
Keywords: deposits, loans, profitability, savings